Pengaruh Persepsi Kemudahan Penggunaan Terhadap Minat Pengguna Financial Technology Berdasarkan Teori Technology Acceptance Model (TAM) - Syam, Yasmin Az Zahra; Hutapea, Riauli Susilawaty (Jurusan Akuntansi Politeknik Negeri Bandung, 2024)
The emergence of financial technology or Fintech provides many benefits and conveniences. One of them is digital payment systems such as Go-Pay, OVO and DANA that make the transaction process easier. In using a technology requires the interest of the user. Determine the effect of perceived ease of use on the interest of Fintech users by using the TAM theory approach is the purpose of this study. The research sample is 110 respondents of Fintech users in Garut City. Simple linear regression analysis is used in data analysis techniques. Thec resultsc ofc thec studyc stated thatc ease of use had a positivec andc significantc effectc onc the interestc ofc Fintech users in Garut City with a large influence of 69.1%.